Data-Driven 3D Facial Animation - Deng, Zhigang.; Deng, Zhigang.; Neumann, Ulrich.; Neumann, Ulrich. (Springer London : Imprint: Springer, 2008)
"Data-Driven 3D Facial Animation" systematically describes the emerging data-driven techniques developed over the last ten years or so. Although data-driven 3D facial animation is used more and more in animation practice, to date there have been very few books that specifically address the techniques involved. Comprehensive in scope, the book covers not only traditional lip-sync (speech animation), but also expressive facial motion, facial gestures, facial modeling, editing and sketching, and facial animation transferring. It provides an up-to-date reference source for academic research and for professionals working in the facial animation field. An edited volume, the book brings together contributions from leading researchers and practitioners working in both academia and in the leading animation studios.